Building Community Pharmacy Work System Capacity for Medication Therapy Management - Jon C. Schommer; Katerina Goncharuk; Andrea L. Kjos; Marcia M. Worley; James A. Owen (INNOVATIONS in Pharmacy, 2012)
Questions within and outside of the pharmacy profession frequently arise about a community pharmacy's capacity to provide patient-care services and maximize contributions to public health. It is surmised that community pharmacy locations must possess specific attributes and have identifiable resources within the location to effectively initiate and optimize their capacity to deliver patient care services in conjunction with medication distribution and other services. The purpose of this paper is to describe three research domains that can help pharmacies make the transition from "traditional" business models to "patient care centered" practices: (1) Work System Design, (2) Entrepreneurial Orientation, and (3) Organizational Flexibility. From these research domains, we identified 21 Work System Design themes, 4 dimensions of Entrepreneurial Orientation, and 4 types of Organizational Flexibility that can be used in combination to assist a practice location in transforming its business model to a "patient care centered" practice. The self-assessment tools we described in this paper could help realign an organization's activities to initiate and optimize capacity for patient care.